ANALISIS SIMBOLIK PERAHU SANDEQ DAN KEARIFAN LOKAL DI POLEWALI MANDAR - Ulya Sunani (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2018)
This study aims to open the meaning of the parts of the sandeq boat artifact and to unravel the local wisdom of the Mandar tribe in relation to the sandeq boat in Polewali Mandar District. The approach in this study is qualitative, describing Sandeq boat based on in-depth interviews, observation, documentation and analyzing Roland Barthes's semiotics to open the meaning of the symbols used by the sandeq boat, then selecting parts of boat artifacts that represent the local wisdom of the Mandar tribe. The results of the study indicate that the parts of the sandeq boat artifact have meaning oriented to identity and form of belief, how Islam and culture are united in their daily activities. Whereas the representation of the local wisdom of the Mandar tribe from the Sandeq boat is in the form of: Understanding of good time, good fortune, appreciation of life, religious and cultural values, and gratitude and sharing.